Socialization of Prevention Patterns of Wild Racing and Suppressing the Number of Traffic Accidents - Ryan Firdiansyah Suryawan; Kamsariaty; Wenny Desty Febrian (PT FORMOSA CENDEKIA GLOBAL, 2023)
The results of this socialization is to provide education to teenagers about the impact of illegal racing activities which are very dangerous for themselves and other drivers. This socialization report can be a reference for creating patterns to prevent illegal racing and traffic accidents. It was found that the role of parents can shape children's personal, commendable attitudes so that they do not violate the law. The aim of the results of this socialization is to educate teenagers about the dangers of illegal racing which can lead to traffic accidents. The method used is community service outreach to communities around areas prone to illegal racing. The results are very useful for evaluating the behavior of teenagers who carry out these negative activities.